Aplicação de controle PI e PID na construção para dispositivo de resfriamento: uma proposta prática - Souza, Matheus Afonso Lima de (2023)
This undergraduate thesis details the development of a prototype for temperature control in a closed environment using PID control techniques. The prototype, housed in an MDF box, regulates a 100-watt lamp via a dimmer to maintain the voltage at 33 Vac. DHT11 and DS18B20 sensors are employed to monitor internal and external temperatures. Real-time sensor data is collected and analyzed through MATLAB-generated graphs. Cooling is facilitated by a 12Vdc fan controlled through PWM signals from the ESP8266 and a BC458 transistor. The PID control implementation, using the Arduino's PID_v1 library, is fine-tuned based on open loop responses and COHEN & COON relationships. Results highlight the energy consumption for cooling concerning the external temperature, establishing an effective temperature control solution for controlled environments.